Systematic Characterization of Brassica napus HIR Gene Family Reveals a Positive Role of BnHIR2.7 in Sclerotinia sclerotiorum Resistance - Mengqi Li; Yuqiao Tang; Mengna Yu; Yonghai Fan; Shahid Ullah Khan; Wei Chang; Xiaodong Li; Siyu Wei; Lijuan Wei; Cunmin Qu; Jiana Li; Kun Lu (Horticulturae, 2022)
Hypersensitive-induced response protein (HIR) is a class of plant immune proteins that play pivotal roles in Sclerotinia sclerotiorum (Lib.) de Bary resistance. However, there has been no systematic investigation and identification of HIR genes in rapeseed (Brassica napus L.). Hence, we identified 50 BnHIR genes and classified them into four groups. Subcellular localization prediction suggested that HIR proteins are mainly localized in the mitochondria. Cis-acting elements involved in light and diverse abiotic stress were found in the promoter regions of BnHIR. The majority of BnHIR genes in Groups 1/3/4 were expressed in most examined tissues, especially in leaves and siliques pericarp, while the BnHIR genes in Group 2 were not or had low expression in all detected tissues. In the case of S. sclerotiorum inoculation, HIR genes in Groups 1/3/4 were strongly induced, especially homologous genes in Group 1, which exhibited different expression patterns. Moreover, overexpression of BnHIR2.7 in Arabidopsis thaliana illustrated its prominent resistance to S. sclerotiorum. Our study provides insight into the evolutionary relationships of the HIR family genes in B. napus and lays the foundation for their resistance to S. sclerotiorum in B. napus.